2017
DOI: 10.1186/s40411-017-0037-x
|View full text |Cite
|
Sign up to set email alerts
|

A genetic algorithm based framework for software effort prediction

Abstract: Background: Several prediction models have been proposed in the literature using different techniques obtaining different results in different contexts. The need for accurate effort predictions for projects is one of the most critical and complex issues in the software industry. The automated selection and the combination of techniques in alternative ways could improve the overall accuracy of the prediction models. Objectives: In this study, we validate an automated genetic framework, and then conduct a sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…Distinctive estimation settings are made with reference to in writing, for example, little informational collection, anomalies, absolute highlights, and missing qualities. Analysts recommend [21,22] that it is more productive to decide the best model in a specific setting instead of deciding the best single model, since estimate models carry on uniquely in contrast to one dataset to other, which makes them precarious. Studies directed on information mining report that group strategies furnish exact outcomes in examination with single strategies as every strategy has quality and shortcoming so joining will moderate the shortcoming.…”
Section: Fig 1 Typical Estimation Process In Scrummentioning
confidence: 99%
See 1 more Smart Citation
“…Distinctive estimation settings are made with reference to in writing, for example, little informational collection, anomalies, absolute highlights, and missing qualities. Analysts recommend [21,22] that it is more productive to decide the best model in a specific setting instead of deciding the best single model, since estimate models carry on uniquely in contrast to one dataset to other, which makes them precarious. Studies directed on information mining report that group strategies furnish exact outcomes in examination with single strategies as every strategy has quality and shortcoming so joining will moderate the shortcoming.…”
Section: Fig 1 Typical Estimation Process In Scrummentioning
confidence: 99%
“…Studies directed on information mining report that group strategies furnish exact outcomes in examination with single strategies as every strategy has quality and shortcoming so joining will moderate the shortcoming. Outfit effort estimation systems might be gathered into two noteworthy classes [22][23][24]16]: homogeneous (e.g., bagging and SVR, RF, MLP, LR, RBF, ANFIS, CBR, RF, SGB, CART, and so forth) and heterogeneous perceived by their base models and blend rules. ANN was utilized most with outfits.…”
Section: Fig 1 Typical Estimation Process In Scrummentioning
confidence: 99%
“…These performance metrics are specific to the software attribute being addressed. It could be classification accuracy, precision, recall and so on for defect prediction models or mean magnitude [17] 14.5 (28.0) S35: Minku [48] 12 (3.3) S66: Jain [79] 10.5 (1.0) S5: Malhotra [18] 14.5 (*) S36: Malhotra [49] 12 (13.3) S67: Dolado [80] 10 (13.2) S6: Hosseini [19] 14.5 (*) S37: Malhotra [50] 12 (1.3) S68: Singh [81] 10 (0.6) S7: De Carvalho [20] 14 (9.0) S38: Shukla [51] 11.5 (6.6) S69: Li [82] 10 (10.4) S8: Canfora [21] 14 (16.0) S39: Liu [52] 11.5 (3.2) S70: Sheta [83] 10 (2.0) S9: Abdi [22] 14 (0.5) S40: Kirsopp [53] 11.5 (8.7) S71: Araujo [84] 10 (3.6) S10: Murrillo-Morera [23] 14 (*) S41: Shan [54] 11.5 (4.4) S72: Malhotra [85] 10 (0.5) S11: Ferrucci [24] 13.5 (2.0) S42: Ferrucci [55] 11.5 (0.7) S73: Malhotra [86] 10 (1.7) S12: Oliveira [25] 13.5 (14.9) S43: Bardsiri [56] 11.5 (11.5) S74: Kumar [87] 10 (1.0) S13: Bardsiri [26] 13.5 (5.7) S44: Basgalupp [57] 11.5 (6.3) S75: Li [88] 9.5 (20.4) S14: Arar [27] 13. of relative error (MMRE) while developing effort estimation models. This specific characteristic makes SBAs ideal for developing SPMs as they can find a good solution by optimising these performance metrics employed as fitness functions (S1, S5, S15, S25, S34, S45).…”
Section: Rq1c: What Characteristics Of Sbas Make Their Application Tomentioning
confidence: 99%
“…All the studies whose QS was <7.5 (50% of the total QS) were rejected. After this step, a total of 93 literature studies [14–106] were selected, which were termed as primary studies of our review. Relevant data pertaining to RQs was extracted from these studies and the obtained results are reported in Section 4.…”
Section: Research Backgroundmentioning
confidence: 99%
“…Juan Murillo Morera designed a frame work for software effort prediction using genetic algorithm. The performance of learning schemes was measured using the metrics Spearman's rank correlation, mean of magnitude relative error, median of magnitude of relative error, standardized accuracy, number of predictions within percentage of actual ones [7]. J S Pahariya et al proposed Genetic Programming based feature selection for software cost estimation.…”
Section: Research Articlementioning
confidence: 99%